2020
DOI: 10.1002/nop2.655
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with loneliness in patients with diabetes mellitus

Abstract: Aim To (a) explore the prevalence of loneliness in patients with diabetes mellitus and (b) identify loneliness‐related factors in the group of hospitalized patients with diabetes mellitus. Design A cross‐sectional study. Methods The study included 248 patients with diabetes mellitus who were staying in six Polish hospitals. A questionnaire including sociodemographic and clinical data, and the Revised UCLA Loneliness Scale (R‐UCLA), was used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Loneliness has been defined as ‘a subjective feeling of the absence of a social network or a companion’ and has been negatively associated with cardiovascular and mental health outcomes [60]. In cancer survivors [61], stroke survivors [62] and diabetes [63], loneliness has impacted health outcomes negatively. We found that reducing loneliness was related to the reflection on challenges prompted by the reflection sheets both individually and in groups.…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness has been defined as ‘a subjective feeling of the absence of a social network or a companion’ and has been negatively associated with cardiovascular and mental health outcomes [60]. In cancer survivors [61], stroke survivors [62] and diabetes [63], loneliness has impacted health outcomes negatively. We found that reducing loneliness was related to the reflection on challenges prompted by the reflection sheets both individually and in groups.…”
Section: Discussionmentioning
confidence: 99%
“…This stigmatization can come both from other people as well as from patients themselves 10 , and people with diabetes may generally show reduced self-esteem 26 . Previous studies have also shown a link between diabetes and loneliness 27 , 28 , with a 20-year follow up study from Sweden confirming that loneliness increases the risk for developing type 2 diabetes. 29 Likewise, social support plays an increased role for people with diabetes 30 , for example, a Dutch study links social isolation, social network and work-related provisions with diabetes type 2, which the authors attribute to symptoms such as tiredness or general feelings of being unwell.…”
Section: Introductionmentioning
confidence: 66%
“…In a study that was conducted by Joensen et al, it was reported that Type 1 and Type 2 diabetes patients experienced more anxiety about COVID-19 and diabetes during the process of pandemic, and most of them felt lonely and needed care for loneliness (Joensen et al, 2020 ). Kobos et al reported that there was no significant difference between the loneliness levels of Type 1 and Type 2 diabetic patients, and patients generally experienced moderate level of loneliness, and approximately one-fifth (16%) of the patients experienced intense loneliness (Kobos et al, 2021 ). Kusaslan Avci conducted a study before the pandemic and, like this study, found that the loneliness levels of individuals with Type 1 and Type 2 diabetes were below the moderate level, while, unlike this study, individuals with Type 1 diabetes had higher loneliness levels (Kusaslan Avci, 2018 ).…”
Section: Discussionmentioning
confidence: 99%